Impact of midwives practices initiation on postpartum haemorrhage reduction in public hospitals in Gaza strip, Palestine - A. M. Abujarad, Sawsan (2018)
The primary Postpartum Haemorrhage (PPH) has occupied the highest factor leading to maternal mortality. PPH is the bleeding from the genital tract of 500 ml or more in the first 24 hours following the delivery of the baby. As compared to the developed countries, maternal mortality in Palestine has been found to be high with the 36.5 death per 100000 births. Poor health care leads to acute and chronic clinical and psychological morbidity. Therefore, there is growing agreement among public health professionals that midwifery has an important contribution to provide a safe delivery and excellent mother and new-born infant care. Applying certain practices in the scope of midwife can lead to a PPH reduction. Consequently, the objectives of this study are to examine the relationship between Breast Feeding (BF), Skin to Skin Contact (SSC) and Active Management of the Third Stage of Labour (AMTSL) on PPH reduction at Gaza strip, Palestine and to examine the impact of these practices (BF, SSC and AMTSL) on the PPH reduction at Gaza strip, Palestine. The population of this study are the midwives working in the labour room at public hospitals in Gaza, Palestine. Quantitative approach has been applied for this study and questionnaire was distributed in the public hospitals of Gaza for the data collection purpose. The response rate was of 82%. SPSS 22 is used as the research instrument to perform the analysis and to study the relationships among the variables. The results of the study demonstrated that the midwife practice initiation (BF, SSC and AMTSL) have significant impact on the PPH reduction. The study contributes in the research field by providing a significant relationship between the practices in the scope of midwife and PPH rate reduction. Contribution of the findings are discussed and recommendations for future research are presented.